Social and Behavioral Difficulties in 10-Year-Old Children With Congenital Heart Disease: Prevalence and Risk Factors - Werninger, Isabelle; Ehrler, Melanie; Wehrle, Flavia M.; Landolt, Markus A.; Polentarutti, Susanne; Valsangiacomo Buechel, Emanuela R.; Latal, Beatrice (Frontiers in Pediatrics, 2020)
Children with congenital heart disease (CHD) may be at increased risk for neurodevelopmental impairments. Long-term behavioral profiles and respective risk factors are less frequently described. The aim of this study was to evaluate multidimensional behavioral outcomes and associated medical, psychological, and social risk factors in children with complex CHD. At 10-years of age, 125 children with CHD were assessed for general behavioral difficulties, for attention deficit hyperactivity disorder (ADHD)-related behavior, and social interaction problems and were compared to normative data. Medical and cardiac factors, IQ, maternal mental health at 4 years of age and parental socioeconomic status were tested as predictors for all behavioral outcomes. Children with CHD showed no significant differences in general behavioral difficulties. However, increased ADHD-related symptoms (p < 0.05) and difficulties in social interaction (p < 0.05) were observed. In 23% of the children, a combination of ADHD-related symptoms and social interaction problems was reported by parents. In multivariate analyses, IQ (p < 0.01) and maternal mental health (p < 0.03) at 4 years of age were found to be predictive for all behavioral outcomes at 10 years while medical and cardiac risk factors were not. Our findings reveal significant difficulties in ADHD-related symptoms and social interaction problems with a significant comorbidity. Behavioral difficulties were not detected with a screening tool but with disorder-specific questionnaires. Furthermore, we demonstrate the importance of maternal mental health during early childhood on later behavioral outcomes of children with CHD. This underlines the importance of identifying and supporting parents with mental health issues at an early stage in order to support the family and improve the child's neurodevelopment.